2017
DOI: 10.21859/mci-01023
|View full text |Cite
|
Sign up to set email alerts
|

The Applicability of the Gail Model in Iranian Population

Abstract: Introduction: Gail model is one of the most important models for the evaluation of breast cancer risk between US white females. According to genetic diversity, there is a possibility of affecting the efficiency of the Gail model in risk assessment of breast cancer among Iranian populations. In this study, the Gail model efficiency in specifying the risk of breast cancer in Iranian population was evaluated. Methods: This was a case-control study. The case group was formed of the referrals to Breast Cancer Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…In India, the studies conducted by Challa et al, (2013), andThomas et al, (2016), both case-control, underestimated the risk within five years of developing breast cancer. The same occurred in Iran in the studies by Omranipour et al, (2015) and Farahmand et al, (2017), which underestimated the risk in women with the disease and found no significant between-group difference in the risk factors evaluated by the model (Table 2).…”
Section: Resultssupporting
confidence: 65%
“…In India, the studies conducted by Challa et al, (2013), andThomas et al, (2016), both case-control, underestimated the risk within five years of developing breast cancer. The same occurred in Iran in the studies by Omranipour et al, (2015) and Farahmand et al, (2017), which underestimated the risk in women with the disease and found no significant between-group difference in the risk factors evaluated by the model (Table 2).…”
Section: Resultssupporting
confidence: 65%
“…Today, there are different models for identifying the risk of breast cancer in women, of which the Gail model is the best known (5). The well-known model of Gail in white American women who have access to mammography is considered as an effective tool to identify the risk of breast cancer, but the use of this model in Iranian women is not very effective because, this model, overestimates the risk of BC in Iranian women (5)(6)(7)(8)(9). There are variations in the relative identi ed risk of individual breast cancer, and these variations may arise from differences in race, taking into account epidemiological diversity and risk factors for breast cancer in populations such as Iranian women (10,11).…”
Section: Introductionmentioning
confidence: 99%